2009
DOI: 10.1007/s00228-009-0728-2
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-led medication reviews and the quality of drug treatment of elderly hospitalized patients

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…In total, 47 published studies and 32 RCT protocols were included in this systematic review. Details on the sources, reasons for exclusion, and selection process are presented in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…In total, 47 published studies and 32 RCT protocols were included in this systematic review. Details on the sources, reasons for exclusion, and selection process are presented in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…After removing 15 papers due to duplicate records and publication dates after 2013, the in- and exclusion criteria were applied to 174 unique publication titles and subsequently to 121 unique abstracts ( Figure 1 ). Of these, 55 full-text publications were reviewed, and 28 were excluded due to: No assessment of clinical significance ( n = 8) [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ], Insufficient data on DRPs ( n = 8) [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], Insufficient data on clinical significance ( n = 5) [ 28 , 29 , 30 , 31 , 32 ], and Wrong study type ( n = 7) [ 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Finally, 27 unique publications were included in the review [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ,…”
Section: Methodsmentioning
confidence: 99%
“…Several intervention studies have revealed that a multidisciplinary approach for older patients could reduce the number of patients with PIMs [ 27 , 28 ] and detect a high proportion of clinically relevant DRPs [ 29 , 30 ]. One previous study conducted in home care settings revealed that a medication review by a community pharmacist could reduce the number of medications, but it was not clear about the relations of pharmacist intervention to drug costs of PIMs [ 31 ].…”
Section: Introductionmentioning
confidence: 99%